Integration of agrotourism model with food crop-horticulture livestock in the Batu Bulan irrigation area, Sumbawa regency - Amrullah; Aida Muspiah; Husnul Jannah; Ida Ayu Widhiantari; Ahmad Yani; Cecep Budiman; Edi Wahyu Satria (Yayasan Siti Widhatul Faeha, 2025)
The development of livestock–crop-integrated agrotourism in the Batu Bulan irrigation area holds significant potential to increase farmers’ incomes, enhance ecological sustainability, and diversify rural economies. This study aims to formulate the most strategic development priorities using SWOT analysis and the Quantitative Strategic Planning Matrix (QSPM). Data were collected through farmer surveys, in-depth interviews, and field observations. The findings indicate that the S–O strategy is the top priority, namely the development of integrated livestock–crop agrotourism packages through institutional strengthening and collaboration among local government, universities, and NGOs. The W–O strategy emphasizes improving human resource capacity in digital marketing, tourism management, and livestock bio-ecology, while the S–T strategy recommends developing environmentally friendly tourism infrastructure such as biogas units, composting facilities, and educational trails. Meanwhile, the W–T strategy focuses on strengthening access to capital, risk management, and governance for smallholder farmers. Overall, the QSPM results highlight that multi-stakeholder collaboration, enhanced human resource competence, and the adoption of environmental technologies are key to the successful implementation of integrated agrotourism models in irrigated agricultural areas. These findings are expected to serve as a reference for local governments, universities, and farmer communities in designing sustainable agrotourism development policies in Indonesia’s agrarian regions